Connectivity and Concentration in Airline Networks: A Complexity Analysis of Lufthansa's Network - Aura Reggiani; Peter Nijkamp; Alessandro Cento (Tinbergen Institute, 2011)
Information, communication and transport networks have always been in a state of flux, while they also influence each other. Extensive research efforts have been made to investigate the dynamics in the structure and use of networks, e.g., by means of network geometries, small-world effects and scale-free phenomena. We will illustrate these new developments on the basis of airline network evolution. The present paper provides a new contribution to the analysis of topological properties of complex airline networks. Using Lufthansa's networks as an example, this paper aims to show the empirical relevance of various network indicators - such as connectivity and concentration - for understanding changing patterns in airline network configurations. After an extensive discussion of various statistical results, a decision-aid method, viz. multi-criteria analysis, is used to investigate the robustness of our findings. The results highlight the actual strategic choices made by Lufthansa for its own network, as well in combination with its partners in Star Alliance.
urn:NBN:nl:ui:31-1871/38521
Keywords: L93; 330; airline networks; complexity; connectivity; concentration; degree distribution; network geometry; multicriteria analysis; Unternehmensnetzwerk; Strategische Allianz; Luftverkehrsgesellschaft; Welt